Theoretical approaches to disharmonic word order - Biberauer, Theresa; Sheehan, Michelle (Oxford University Press, 2013)
This title considers whether any generalisations can be made about word order in language. The chapters, written by international scholars, draw on data from several 'disharmonic' and typologically distinct languages, including Mandarin Chinese, Basque, French, English, Hixkaryana (a Cariban language), Khalkha Mongolian, Uyghur Turkic, and Afrikaans.